Emerging investigator series: a multispecies analysis of the relationship between oxygen content and toxicity in graphene oxide. Issue 6 (5th May 2021) - Barrios, Ana C.; Cahue, Yaritza P.; Wang, Yan; Geiger, Jason; Puerari, Rodrigo C.; Matias, William Gerson; Melegari, Silvia Pedroso; Gilbertson, Leanne M.; Perreault, François
Abstract : The relationship between oxygen content and toxicity in graphene oxide varies between species. Abstract : The toxicity of graphene oxide (GO) has been documented for multiple species. However, GO has variable surface chemistry, and it is currently unclear whether changes in oxygen content impact GO-organism interactions the same way across species. In this study, a modified Hummer's GO (ARGO) was systematically reduced by thermal annealing at 200, 500, or 800 °C and toxicity towards bacteria ( Escherichia coli ), alga ( Scenedesmus obliquus ), cyanobacteria ( Microcystis aeruginosa ), and invertebrates ( Daphnia magna ) was assessed by measuring the effective concentrations inducing 50% inhibition (EC50 ). The EC50 –carbon/oxygen ratio relationships show similar trends for bacteria and invertebrates, where toxicity increases as the material is reduced. Conversely, cyanobacterial inhibition decreases as GO is reduced. Further testing supports differences in cell-GO interactions between bacteria and cyanobacteria. Cyanobacteria showed a decrease in metabolic activity, evidenced by a 69% reduction in esterase activity after ARGO exposure but no oxidative stress, measured by 2′, 7′-dichlorodihydrofluorescein diacetate (H2 DCFDA) fluorescence and catalase activity. In contrast, ARGO induced a 55% increase in H2 DCFDA fluorescence and 342% increase in catalase activity in bacteria. These changes in cell–material interactions propose different mechanisms of action, a physical mechanism occurring in cyanobacteria, and a chemical mechanism in bacteria. The differences in GO toxicity observed in different organisms emphasize the need to differentiate the safe-by-design guidelines made for GO in relation to the potential organisms exposed.